(untitled) (Advances in Applied Mathematics and Mechanics, 2022)
To simulate the incompressible turbulent flows, two models, known as the simplified and highly stable lattice Boltzmann method (SHSLBM) and large eddy simulation (LES) model, are employed in this paper. The SHSLBM was developed for simulating incompressible viscous flows and showed great performance in numerical stability at high Reynolds numbers, which means that this model is capable of dealing with turbulent flows by adding the turbulence model. Therefore, the LES model is combined with SHSLBM. Inspired by the less amount of grids required for SHSLBM, a local grid refinement method is used at relatively high Reynolds numbers to improve computational efficiency. Several benchmark cases are simulated and the obtained numerical results are compared with the available results in literature, which show excellent agreement together with greater computational performance than other algorithms.